A new perspective and assessment measure for common dissociative experiences: 'Felt Sense of Anomaly'. - Emma Černis; Esther Beierl; Andrew Molodynski; Anke Ehlers; Daniel Freeman (PLoS ONE)
Background Dissociative experiences occur across a range of mental health disorders. However, the term 'dissociation' has long been argued to lack conceptual clarity and may describe several distinct phenomena. We therefore aimed to conceptualise and empirically establish a discrete subset of dissociative experiences and develop a corresponding assessment measure. Methods First, a systematic review of existing measures was carried out to identify themes across dissociative experiences. A theme of 'Felt Sense of Anomaly' (FSA) emerged. Second, assessment items were generated based on this construct and a measure developed using exploratory (EFA) and confirmatory (CFA) factor analyses of 8861 responses to an online self-report survey. Finally, the resulting measure was validated via CFA with data from 1031 patients with psychosis. Results 'Felt sense of anomaly' (FSA) was identified as common to many dissociative experiences, affecting several domains (e.g. body) and taking different forms ('types'; e.g. unfamiliarity). Items for a novel measure were therefore systematically generated using a conceptual framework whereby each item represented a type-by-domain interaction (e.g. 'my body feels unfamiliar'). Factor analysis of online responses found that FSA-dissociation manifested in seven ways: anomalous experiences of the self, body, and emotion, and altered senses of familiarity, connection, agency, and reality (Χ2 (553) = 4989.435, p<0.001, CFI = 0.929, TLI = 0.924, RMSEA = 0.052, SRMR = 0.047). Additionally, a single-factor 'global FSA' scale was produced (Χ2 (9) = 312.350, p<0.001, CFI = 0.970, TLI = 0.950, RMSEA = 0.107, SRMR = 0.021). Model fit was adequate in the clinical (psychosis) group (Χ2 (553) = 1623.641, p<0.001, CFI = 0.927, TLI = 0.921, RMSEA = 0.043, SRMR = 0.043). The scale had good convergent validity with a widely used dissociation scale (DES-II) (non-clinical: r = 0.802), excellent internal reliability (non-clinical: Cronbach's alpha = 0.98; clinical: Cronbach's alpha = 0.97), and excellent test-retest reliability (non-clinical: ICC = 0.92). Further, in non-clinical respondents scoring highly on a PTSD measure, CFA confirmed adequate model fit (Χ2 (553) = 4758.673, CFI = 0.913, TLI = 0.906, RMSEA = 0.052, SRMR = 0.054). Conclusions The Černis Felt Sense of Anomaly (ČEFSA) scale is a novel measure of a subset of dissociative experiences that share a core feature of FSA. It is psychometrically robust in both non-clinical and psychosis groups.